Superfluous Hospital Expenditure Associated with Unnecessary Renal Cyst Surveillance. Issue 1 (January 2020) - Wang, Michael; Ng, Mitchell; Bukavina, Laura; Mahran, Amr; Mishra, Kirtishri; Buzzy, Christina; Garrels, Kristina; Ponsky, Lee; Nguyen, Carvell
Abstract: Introduction: To measure the cost expenditure associated with renal cyst surveillance, we examined renal cyst surveillance patterns at our institution and the associated surplus cost of unindicated imaging. Methods: Patients with a renal cyst diagnosis between January 2017 and June 2018 were identified and their respective clinical and imaging data were reviewed for surveillance patterns. Unindicated renal cyst followup was defined by the Radiographic Society of North America and Canadian Urological Association. Total unnecessary expenditures from ultrasound, computerized tomography and magnetic resonance imaging were calculated using cost of services provided by FAIRHealth Consumer®. Univariate and multivariable analyses were performed with statistical significance defined as p <0.05. Results: A total of 1, 100 patients were identified, with a random sample of 292 selected for analysis. Of these patients 271 were diagnosed with Bosniak I and II renal cysts. Overall 52 (19%) of these patients underwent unindicated imaging, which totaled 60 ultrasound, 19 computerized tomography and 5 magnetic resonance imaging. A total superfluous cost of $347, 501 was calculated when extrapolating to the entire nephrology cohort. Multivariable analysis showed higher unindicated imaging for Bosniak II renal cysts compared to Bosniak I renal cysts (OR 3.2, 95% CI 1.6–6.3, p <0.001) and decreased surveillance imaging for African American compared to Caucasian patients (OR 0.29, 95% CI 0.13–0.59, p <0.001). Conclusions: Among patients diagnosed with Bosniak I and II renal cysts, unnecessary surveillance imaging was associated with higher hospital costs. Adherence to strict renal imaging guidelines for renal cysts can significantly reduce unnecessary expenditures, patient anxiety and patient harm.